PREPARATION, DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC METHOD FOR THE ESTIMATION OF APIGENIN IN APIGENIN–HYDROGENATED SOY PHOSPHATIDYLCHOLINE (HSPC) COMPLEX - P, Arun; T, Amol; Darshan, T (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To Develop simple, sensitive UV – visible spectrophotometric method for determination of Apigenin (APG) in Apigenin – Hydrogenated Soy Phosphatidylcholine (HSPC) Complex. Methods: The APG –HSPC Complex (phytosomes) were prepared by dissolving both APG and HSPC in 20 ml mixture of 1, 4 – dioxane: methanol at a ratio of (14:6) by refluxing and complex produced by solvent evaporation method. The spectrophotometric detection of APG was done at the absorption maximum (λ max) of 335 nm and 268 nm using methanol as solvent. The developed method was validated as per International Conference on Harmonization (ICH) guidelines. Results: APG content in APG – HSPC Complex was found to be 82.86±0.90% and 76.89±0.84% at 335 nm and 268 nm. APG exhibited good linearity in concentration range 2 – 12 µg/ml (r2>0.99) at 335 nm and 2 – 14 µg/ml (r2>0.99) at 268 nm. Precision and mean recoveries were found to be in the range of (% RSD 0.0981 & 0.0989) and (% RSD 0.0829 & 0.1116) and 94.67±2.52 % & 86.56±1.90 % at 335 nm and at 268 nm. The limit of detection (LOD) and limit of quantification (LOQ) was found to be (0.0106µg/ml & 0.0322µg/ml) and (0.0259µg/ml & 0.0757µg/ml) respectively. Conclusion: The developed method was found to be minimal, specific, economic, reliable, accurate, precise, and reproducible that used as a quality control tool for analysis of APG.